Classroom Management Styles of Grade 6Teachers at Caloocan North Elementary School and its Impact on Academic Performance (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Classroom management style creates a set of expectations used in an organized classroom environment. An effective classroom management style paves the way for the teacher to engage the students in learning. In addition to being highly knowledgeable in the subject matter,teachers also need to know how to manage classroom dynamics effectively. This entails organizational and disciplinary skills, which help make different types of classroom interactions. A well-managed classroom provides an environment in which teaching andlearning can flourish. However, a well-managed classroom does not only come out of anywhere. Creating a conducive classroom climate takes a good deal of effort. The person who is the most responsible for creating this atmosphere is the teacher. The researchers utilized the descriptive method design in collecting information about the classroom management styles of Grade 6 teachers in Caloocan North Elementary School and its impact on academic performance. The researchers chose 15 Grade 6 teachers in Caloocan North Elementary School as respondents. The researchers also used the purposive sampling technique. The researchers formulated the following results. The majority of the respondents used a democratic style of teaching for their classroom management. Different classroom management styles, such as authoritarian, democratic, permissive, and indulgent, that affect the academic performance of the pupils exist. There are best practices, such as cognitive development, affective development, and psychomotor development, that are used by the respondents for the performance of the students. The respondents suggested the use of the following techniques and strategies to improve the teaching styles: keeping parents informed, providing positive reinforcement, providing their students with firm but fair classroom rules, and consistently adhering to the consequences of breaking rules. Based on the summary of findings and conclusion drawn, the following are hereby recommended. Teachers should use a democratic style instead of an authoritarian, permissive, and indulgent style for effective classroom management. Teachers should innovate new techniques and strategies to improve the academic performance of the students. Parents should also do a follow-up on the improved behavior of the values formation of students. Similar studies should also be conducted to verify the results of this research.
Keywords: classroom management styles, academic performance